Synthesis and Pyrolysis of Fullerenol‐stabilized Pt Nanocolloids as a unique Approach to Pt‐doped Carbon. Issue 16 (30th June 2021) - Cabello, Mark Kristan Espejo; Uetake, Yuta; Yao, Yu; Kuwabata, Susumu; Sakurai, Hidehiro
Abstract: An aqueous colloidal dispersion of Pt nanoparticles (NPs) stabilized by fullerenol C60 (OH)12 (Pt:C60 (OH)12 ) was successfully synthesized via liquid‐phase chemical reduction. The subsequent pyrolysis of Pt:C60 (OH)12 at different temperatures was conducted to afford Pt‐doped carbon with different chemical compositions (Pt:C60 n ). X‐ray absorption spectroscopy (XAS) and Infrared (IR) absorption spectroscopy and thermogravimetric measurements revealed that the thus‐prepared nanocomposite consists of Pt NPs and high valent Pt‐C60 (OH)12 complex. One distinct feature of C60 (OH)12 matrix as catalyst support is the suppression of size growth of Pt NPs during the pyrolysis up to 300 °C. Electrochemical experiments using cyclic voltammetry (CV) and linear sweep voltammetry (LSV) were performed to find that Pt:C60 300 (pyrolyzed at 300 °C) exhibited higher activity than others, that was attributed to the π‐extended feature of the as‐obtained carbon. Abstract : Pt nanoparticles deposited on π‐extended carbon support is fabricated through pyrolysis of newly prepared colloidal Pt:C60 (OH)12 precursor. Insights into the modification approach revealed interesting features of C60 (OH)12 around the Pt NP. The pyrolytic carbon support changes from broken π‐state to π‐extended state. Such a feature contributes to the controlled particle growth and surface activity of Pt nanoparticles.